Rational use of water resources in Cyprus - Chimonidou D.; Polycarpou P.; Vassiliou L. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
The scarcity of water together with the high cost associated with collecting and using the limited surface rainwater for irrigation, has become a real constraint for Cyprus irrigated agriculture. This is why, particular emphasis is placed on the water use efficiency and modern irrigation technology. Modern irrigation systems have been used in Cyprus agriculture for the last 40 years. It is estimated that currently over 95 percent of the total irrigated land of the country is being served by modern irrigation methods. Recently, particular emphasis has been laid on protected cultivation and more specifically on the cultivation of vegetables and flowers in substrates and soilless cultures (closed and open systems with minimum drainage). At the Agricultural Research Institute, the use of local materials i.e. perlite, mixtures of perlite with pomace, almond shells, pine bark etc. have been tried successfully. In this paper, results of the application of modern techniques, hydroponic cultures, re-circulation of irrigation water and nutrient solution in closed systems and control of the climatic conditions in the greenhouse are discussed. In making the supply meet the demand the Government policy has encouraged and adopted management measures as water rationing, increase in public awareness for water conservation measures and water pricing for improvements in the water use efficiencies. The main measures, as well as the new Government water policies, are discussed in this paper.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)